Combination of Propolis Extract (Trigona Sp) and Ginger Rhizome (Zingiber Officinale Roscoe) as Alternative Antibiotics against Escherichia Coli In Vitro - Abdul Wahid Jamaluddin; Muhammad F. Mursalim; Andi M. S. Apada (Indonesian Journal of Pharmaceutical Science and Technology, 2019)
Escherichia coli is a gram negative bacterium which is a normal flora in the digestive tract. In birds, this bacterium causes a disease known as colibasillosis. Antibiotics are generally used, but excessive use will cause residues and antibiotic resistance. To avoid resistance or residue, an alternative treatment is needed. The combination of propolis and ginger extract is very promising to develop because both have a synergistic effect as antimicrobials. The research aims to determine the effect of the combination extract on Escherichia coli bacteria in vitro. We used 8 groups which contain combinations of propolis and ginger extract. We used amoxicillin disk as a positive control, 1% Na CMC as a negative control. The results showed a combination of ginger and propolis extract showed good inhibitory activity against Escherichia coli in all groups> 6mm., and the highest inhibitory activity was K3 (5% propolis combination and 15% ginger extract) with 8.7 mm. The combination of propolis and ginger extract has the potential to be used as an alternative antibiotic to prevent antibiotic resistance from synthetic antibiotics.Keywords: alternative antibiotics, combination extracts, Escherichia coli, ginger, in vitro, propolis